2006
DOI: 10.1111/j.1469-8137.2006.01788.x
|View full text |Cite
|
Sign up to set email alerts
|

Weed response to herbicides: regional‐scale distribution of herbicide resistance alleles in the grass weedAlopecurus myosuroides

Abstract: Summary• Effective herbicide resistance management requires an assessment of the range of spatial dispersion of resistance genes among weed populations and identification of the vectors of this dispersion.• In the grass weed Alopecurus myosuroides (black-grass), seven alleles of the acetyl-CoA carboxylase ( ACCase ) gene are known to confer herbicide resistance. Here, we assessed their respective frequencies and spatial distribution on two nested geographical scales (the whole of France and the French administ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
111
3

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 73 publications
(121 citation statements)
references
References 35 publications
7
111
3
Order By: Relevance
“…Alopecurus myosuroides containing 1781Leu/ Leu ACCase also showed a fitness advantage in seed germination (Délye et al, 2013). In addition, wide spread of Ile1781Leu ACCase in L. rigidum and across grass species may suggest that Ile1781Leu ACCase usually cause no fitness cost (Délye et al, 2005;Zhang and Powles, 2006;Menchari et al, 2006;Liu et al, 2007;Yu et al, 2007). In this paper, seeds containing homozygous 1781Leu/Leu ACCase showed a fitness advantage under salt and osmotic stress, but no fitness variation in optimal experimental condition.…”
Section: Fitness Cost Depends On the Mutant Accase Allelementioning
confidence: 77%
“…Alopecurus myosuroides containing 1781Leu/ Leu ACCase also showed a fitness advantage in seed germination (Délye et al, 2013). In addition, wide spread of Ile1781Leu ACCase in L. rigidum and across grass species may suggest that Ile1781Leu ACCase usually cause no fitness cost (Délye et al, 2005;Zhang and Powles, 2006;Menchari et al, 2006;Liu et al, 2007;Yu et al, 2007). In this paper, seeds containing homozygous 1781Leu/Leu ACCase showed a fitness advantage under salt and osmotic stress, but no fitness variation in optimal experimental condition.…”
Section: Fitness Cost Depends On the Mutant Accase Allelementioning
confidence: 77%
“…In previous studies, these mutations are the most frequently observed in different grass weed species [19,20].…”
Section: Molecular Bases Of Resistance To Accase-and Als-inhibiting Hmentioning
confidence: 84%
“…19,20 Following technology evolution, allele-specific PCR has been at the basis of 'hi-tech', high-throughput assays implementing quantitative PCR. 21,22 Other genotyping techniques allowing high-throughput detection of mutations at known positions have also been used to develop pesticide resistance diagnosis, such as MALDI-TOF, 23 TaqMan, 24,25 SimpleProbe, 26 DNA microarrays 27 or SNaPshot. 28 A common feature of all the techniques described above is that they only provide information about the mutation(s) present at a given nucleotide position or codon, which generally requires identification of the mutation(s) in question beforehand.…”
Section: Introductionmentioning
confidence: 99%